Persepsi Wisatawan terhadap Keberadaan Saung Angklung Udjo sebagai Bentuk Eksistensi Kebudayaan Sunda - Ferdiansyah, Putra; Aulia, Syifa; Munazilah, Lediana; Juliansyah, Juliansyah; Solehah, Solehah; Nafiah, Noni; Sofian, Robby; Oktaviani, Wilda (Lembaga Yasin AlSys, 2022)
This study aims to determine the perception of tourists to the existence of Saung Angklung Udjo as a form of existence of Sundanese culture. This research was conducted at Saung Angklung Udjo cultural tourism. The research method used is a descriptive analysis study method with a qualitative approach, the respondents in this study were the tourists from Saung Angklung Udjo and the manager. The data collection techniques used were observation, interviews, and documentation. Based on the results of research conducted by researchers about tourist perceptions of the existence of Saung Angklung Udjo as a form of existence of Sundanese culture, namely the role of Saung Angklung Udjo in Introducing Sundanese Culture to local and international tourists in the form of education, and especially in terms of its cultural appeal. As for the impact, the presence of Saung Angklung Udjo has a positive impact on tourists, managers and the community, where Saung Angklung Udjo can invite the community to preserve Sundanese culture.